2015
DOI: 10.1590/2317-1545v37n4149431
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the period for evaluation of the physiological quality of newly harvested black oat seeds

Abstract: -Black oat seeds exhibit dormancy when newly harvested, which is normally broken in the interval between harvest and the sowing season. Dormancy, however, becomes a limiting factor in the estimate of the physiological quality of the seeds soon after harvest, requiring the use of methods for breaking dormancy, which delays making decisions in regard to the destination of seed lots. Given this situation, the aim of the present study was to evaluate the possibility of reducing the period for obtaining results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…This described behavior of seeds is characteristic of some species soon after harvesting and includes black oats, due to the process of primary or innate dormancy that is genetically programmed into the mother plant as a function of environmental conditions. Overcoming dormancy can occur over time under conditions of low seed moisture content, culminating in the increase of the germination percentage in storage (Grzybowski et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This described behavior of seeds is characteristic of some species soon after harvesting and includes black oats, due to the process of primary or innate dormancy that is genetically programmed into the mother plant as a function of environmental conditions. Overcoming dormancy can occur over time under conditions of low seed moisture content, culminating in the increase of the germination percentage in storage (Grzybowski et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Lemes et al (2014), Carbonera (2016) e Mattioni et al (2014) verificaram que a temperatura de 20°C pode ser utilizada para a germinação (acima de 90%) de sementes de aveia branca. Grzybowski et al (2015) verificaram que o esfriamento inicial das sementes de aveia preta afeta positivamente na germinação (acima de 90%), utilizando rolo de papel. Resultado semelhante ao que foi encontrado no presente trabalho, em que a temperatura de 5°C atuou de forma benéfica na germinação.…”
Section: Resultsunclassified
“…In the evaluation, the percentage of normal seedlings, abnormal seedlings and dead seeds was determined (Brazil, 1992(Brazil, , 2009. Work done by Grzybowski et al (2015) showed that predrying may be carried out for five days. The tetrazolium test which determines the feasibility of seeds also followed the criteria established in the rules for seed testing.…”
Section: Methodsmentioning
confidence: 99%